2022
DOI: 10.1371/journal.pcbi.1010330
|View full text |Cite
|
Sign up to set email alerts
|

Drug repurposing based on a quantum-inspired method versus classical fingerprinting uncovers potential antivirals against SARS-CoV-2

Abstract: The COVID-19 pandemic has accelerated the need to identify new antiviral therapeutics at pace, including through drug repurposing. We employed a Quadratic Unbounded Binary Optimization (QUBO) model, to search for compounds similar to Remdesivir, the first antiviral against SARS-CoV-2 approved for human use, using a quantum-inspired device. We modelled Remdesivir and compounds present in the DrugBank database as graphs, established the optimal parameters in our algorithm and resolved the Maximum Weighted Indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
0
8
0
2
Order By: Relevance
“…These patients appeared to be self-reporting significant improvement while on treatment. This treatment, as outlined above, has ingredients that would relieve oxidative stress ( Maes et al, 2011 , 2012a , 2012b , 2021 ; Dennis et al, 2021 ; Kumar et al, 2020 ; Wu, 2020 ; Al-Hakeim et al, 2023 ; Fukuda et al, 1994 ; Paul et al, 2021 ; Takemoto et al, 2021 ; Gould et al, 2010 , 2011 , 2015 ; Prousky, 2007 ; Rusznak et al, 2000 ; Buhl et al, 1990 ; Dekhuijzen, 2004 ; Straface et al, 2000 ; Bridgeman et al, 1991 ; Hagiwara et al, 2000 ; Paulin et al, 2017 ; Lima et al, 2013 ; Juergens et al, 2003 , 2004 , 2018 , 2020 ; Rhoden et al, 2004 ; Kennedy-Feitosa et al, 2016 ; Dahham et al, 2015 ; Machado et al, 2018 ; Kim et al, 2015 ), known to be disturbed in ME/CFS and Long COVID; attenuate NF-κB signaling ( Kim et al, 2015 ; Greiner et al, 2013 ; Francomano FC et al, 2019 ; Oka et al, 2000 ; Sudhoff et al, 2015 ; Yadav and Chandra, 2017 ; Cantin et al, 2000 ; Lou and Kaplowitz, 2007 ; Xu et al, 2016 ), which would decrease T-cell receptor (TCR) signaling and potentially reverse CD8 T-cell dysfunction; and act directly against pathogens, including viruses, bacteria and fungi ( Dahham et al, 2015 ; Holroyd et al, 1993 ; Nencioni et al, 2003 ; Roederer et al, 1990 ; Geiler et al, 2011 ; Yang et al, 2010 ; Li et al, 2016 ; Astani et al, 2011 ; Pajaro-Castro et al, 2015 ; Cavar Zeljkovic et al, 2022 ; Kim et al, 2022 ; Jimenez-Guard...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These patients appeared to be self-reporting significant improvement while on treatment. This treatment, as outlined above, has ingredients that would relieve oxidative stress ( Maes et al, 2011 , 2012a , 2012b , 2021 ; Dennis et al, 2021 ; Kumar et al, 2020 ; Wu, 2020 ; Al-Hakeim et al, 2023 ; Fukuda et al, 1994 ; Paul et al, 2021 ; Takemoto et al, 2021 ; Gould et al, 2010 , 2011 , 2015 ; Prousky, 2007 ; Rusznak et al, 2000 ; Buhl et al, 1990 ; Dekhuijzen, 2004 ; Straface et al, 2000 ; Bridgeman et al, 1991 ; Hagiwara et al, 2000 ; Paulin et al, 2017 ; Lima et al, 2013 ; Juergens et al, 2003 , 2004 , 2018 , 2020 ; Rhoden et al, 2004 ; Kennedy-Feitosa et al, 2016 ; Dahham et al, 2015 ; Machado et al, 2018 ; Kim et al, 2015 ), known to be disturbed in ME/CFS and Long COVID; attenuate NF-κB signaling ( Kim et al, 2015 ; Greiner et al, 2013 ; Francomano FC et al, 2019 ; Oka et al, 2000 ; Sudhoff et al, 2015 ; Yadav and Chandra, 2017 ; Cantin et al, 2000 ; Lou and Kaplowitz, 2007 ; Xu et al, 2016 ), which would decrease T-cell receptor (TCR) signaling and potentially reverse CD8 T-cell dysfunction; and act directly against pathogens, including viruses, bacteria and fungi ( Dahham et al, 2015 ; Holroyd et al, 1993 ; Nencioni et al, 2003 ; Roederer et al, 1990 ; Geiler et al, 2011 ; Yang et al, 2010 ; Li et al, 2016 ; Astani et al, 2011 ; Pajaro-Castro et al, 2015 ; Cavar Zeljkovic et al, 2022 ; Kim et al, 2022 ; Jimenez-Guard...…”
Section: Resultsmentioning
confidence: 99%
“…All the components in this nebulized agent have been reported to have broad direct anti-viral properties against several viruses, including several that routinely produce respiratory symptoms, including parainfluenza-1, influenza A (H5N1), herpes simplex virus type-1 (HSV-1) and type-2 (HSV-2), human immune deficiency virus (HIV-1), and dengue virus 2 (DENV-2) ( Holroyd et al, 1993 ; Nencioni et al, 2003 ; Roederer et al, 1990 ; Geiler et al, 2011 ; Yang et al, 2010 ; Li et al, 2016 ; Astani et al, 2011 ; Pajaro-Castro et al, 2015 ). 1,8-cineole, β-caryophyllene and methylcobalamin each have antiviral properties to SARS-CoV-2 ( Cavar Zeljkovic et al, 2022 , Jimenez-Guardeno et al, 2022 , Kim et al, 2022 ). β-caryophyllene has broad spectrum antibacterial properties (in vitro) against several bacterial species, including S. aureus, K. pneumoniae, and P. aeruginosa, and in vivo for M .…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 282 participants (age, median [range], 55 [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , …”
Section: Resultsunclassified
“…For instance, remdesivir, an intravenous RdRp inhibitor developed for the Ebola virus, and molnupiravir, an oral drug designed for the influenza virus, are commonly used to treat symptomatic COVID-19 patients [ 17 , 18 , 19 , 20 ]. Since in silico (computer simulations), in vitro (laboratory experiments), and in vivo (studies performed on living organisms) evidence has demonstrated the efficacy of RdRp inhibitors against SARS-CoV-2 variants, it is unsurprising that these drugs have been successful across the various waves of SARS-CoV-2 strains [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. In addition to the exploration of RdRp inhibitors as COVID-19 disease treatments, there has also been interest in using anti-RdRp agents in a prophylactic manner (i.e., to prevent disease and/or provide some protection before an exposure may occur).…”
Section: Introductionmentioning
confidence: 99%
“…Достаточное потребление витамина B12 необходимо и для производства антител и клональной экспансии [17,21,39], а его дефицит связан с более низкими концентрациями циркулирующих лимфоцитов и измененными ответами на основе антител [40].…”
Section: обзорыunclassified